Identification and Calibration of Measuring Scales Accuracy in Trading at The Tigabinanga Fruit Market and Socialization of the Importance of Calibration at SMAN 1 Tigabinanga - Ginting, Junedi; Hakim, Lukman; Nufus, Syukratun; Parlindungan; Hotlan Siahaan (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The accuracy of measuring instruments is very important in every use of tools, both in trade transactions and other fields that require measuring instruments. In the field of trade, the use of accurate measuring scale in a transaction is considered very important in determining the final amount that must be paid by consumers. At the Tigabinanga fruit market, differences in measurement values were found with an accuracy of up to 600 grams. Therefore, to maintain the accuracy of the scale measurements, regular re-calibration must be carried out. The introduction of the re-calibration process was carried out by Lecturers and assisted by students of the Faculty of Vocational Studies, University Sumatera Utara (USU) in two places, namely the Tigabinanga Fruit Market and socialization to students of SMAN 1 Tigabinanga. This activity is a community service activity from the USU Vocational Faculty that was well received by traders and students. The lack of awareness of traders to re-calibrate and the small number of scales found that have a valid calibration stamp show that the importance and provide a real effect of this socialization. In addition, the introduction of calibration was also carried out students of SMAN 1 Tigabinanga, the students were also considered as right target, where students showed enthusiasm and deep curiosity about the calibration and recalibration processes which are important in the use of simple measuring instruments, even on market scales.